Fangirl. 3 - Rowell, Rainbow; Rowell, Rainbow (Fangirl : the manga, 2023)
""The graphic novelization of Fangirl is a beautiful, contemplative, and fun reading experience."--Women Write About Comics. Cath is a Simon Snow fan. Okay, everybody is a Simon Snow fan, but for Cath, being a fan is her life. Cath's sister has mostly grown away from fandom, but Cath just can't let go...Everything in Cath's offline life is going wrong. Just when she's started to realize her feelings for Levi, she sees him kissing someone else. Plus, her writing partner, Nick, is acting strange, and her twin sister, Wren, is suddenly making time for their mother--the same woman who walked out of their lives ten years ago! When their dad ends up in the hospital, Cath decides it's time to rethink her plans for the future. But how can she leave the past behind when it keeps showing up at her door?"--Amazon.